Self-efficacy in romantic relationships: direct and indirect effects on relationship maintenance and satisfaction. (January 2016) - Weiser, Dana A.; Weigel, Daniel J.
Abstract: Self-efficacy in romantic relationships is consistently associated with relationship satisfaction. We propose that one reason for this association may be high self-efficacy individuals' greater willingness to carry out relationship maintenance behaviors (positivity, openness, assurances, networks, & tasks). The current study explores whether relationship maintenance behaviors mediate the association between self-efficacy in romantic relationships and relationship satisfaction. Participants currently in romantic relationships (n = 187) completed an online survey. Our findings indicate that relationship maintenance behaviors do indeed mediate the association between self-efficacy and relationship satisfaction. In other words, individuals who believe they are more competent relationship partners report engaging in higher levels of all five relationship promoting behaviors, and these behaviors are then associated with greater levels of relationship satisfaction. In addition to this mediated relationship, a direct effect was also found for self-efficacy and satisfaction. These findings suggest that self-efficacy in romantic relationships has implications for relationship satisfaction and relationship promoting behaviors at least partially explain this association. Highlights: Relationship self-efficacy positively associated with relationship satisfaction Greater relationship self-efficacy associated with higher relationship maintenance Relationship maintenance mediates association between self-efficacy and satisfaction. Relationship self-efficacy had significant direct and mediated effects on satisfaction.